PEMBELAJARAN TEMATIK-EKSPLORATIF-DEMOKRATIK (TED) DALAM FISIKA DENGAN TEMA PERMAINAN LAYANG-LAYANG - Kapulika, Gloria Christiany; Tumangkeng, Jeane V; Rende, Jeane Cornelda (LPPM Politeknik Saint Paul Sorong, 2024)
Kite is a traditional game that can be utilised as a learning resource. The purpose of this study was to determine the results of exploration of physics concepts in kite games through Thematic-Explorative-Democratic Learning (TED-L). This research used descriptive qualitative method. This research was conducted at SMA Negeri 2 Siau Timur, in February 2024. The subjects of this study were students of class XII IPA SMA Negeri 2 Siau Timur, with the object of research being the kite game. Data collection techniques using exploration sheets, observation and interviews. The data collected will be analysed descriptively. Based on the results of the exploration of physics concepts carried out by students of class XII IPA SMA Negeri 2 Siau Timur on kites using Thematic-Explorative-Democratic Learning (TED-L), the results of the identification of science concepts namely Bernoulli's Law, Lifting force, Potential energy, Kinetic energy, Mechanical energy, Holding force, Rope tension force, Effort, Calorific, Kinetic friction force, Pressure, and equilibrium through six facts, issues, phenomena. Based on the results of the study, it can be concluded that the results of the exploration of physics concepts carried out by students on kite games through Thematic-Exploratory-Democratic Learning (TED-L) get a good category from five groups based on six indicators and six facts, issues, phenomena Suggestions for further research For educators to pay attention to the ability to explore physics concepts carried out by students and for researchers to conduct research using other local wisdom themes such as tourist attractions, regional dances, or other traditional games.